Estudo da Influência do Número de Acidez Total e Teor de Enxofre Total nas Frações Destiladas no Processo de Corrosão em Aços do Tipo AISI 1020 e AISI 316 - Almeida, Vinícius Mansur Dose Lage de (2014)
The damage caused by corrosive equipment present in oil refineries, during distillation processes, were first described in 1920. In the literature, extensive references are reporting studies of corrosive processes involving both naphthenic acids such as sulfur compounds, however, very few sources of study involving simultaneously these both. In this study, we chose two types of oils: The oil “A” - high in sulfur; and oil “B” with high acidity. Then there was made a blend 50/50 by volume so getting the oil “C” in order to check the influence of both acidity as the sulfur in the corrosion process by cutting these oils. After distillation of the three samples, the derivatives were characterized and subjected to laboratory corrosion tests. The cuts of “A” oil showed levels of sulfur and corrosion rates increased in relation to the final temperature of derivatives, it was presented a maximum carrion rate of 1,66 mm/year and corrosion products such as troilite (FeS) and pyrrhotite (Fe1-xS). Fractions of “B” showed high values of TAN in a temperature range of 220-400 °C and corrosion rates were 0,83 mm/year for this range of temperature; the corrosion products found were iron oxide (Fe2O3) and goetite (a-FeOOH). Finally, derivatives of blend “C” had properties intermediaries which corroborating to the cuts of this oil presented rates less than 0,50 mm/year up to temperature of 300 °C, thus exposing the efficiency in utilizing the technique of mixtures of oils for refining.